The Optimizing of Digital Marketing to Increase Brand Awareness of Sudut Lombok - Ningrum, Intan Cahya; Megawati, Lokita Rizky; Nurhayati, Popong (Jurnal Aplikasi Bisnis dan Manajemen, 2023)
Companies are utilizing the increasing technological and information development to conduct digital marketing activities. Sudut Lombok is a business that operates digital marketing to increase its brand awareness to potential customers. The purpose of this research is to (1) identify digital marketing strategies that Sudut Lombok has carried out in building its brand awareness, (2) measure the level of brand awareness of Sudut Lombok in potential customers, and (3) determine the solution proposed implementation of the right digital marketing strategy in increasing brand awareness. This study used the marketing mix 4C in identifying Sudut Lombok’s marketing activities and brand awareness pyramid to measure the level of brand awareness of Sudut Lombok. The results show that the right digital marketing strategies, brand awareness, and digital marketing solutions can optimize the marketing media used by Sudut Lombok. Keywords: brand awareness, brand awareness pyramid, digital marketing, marketing mix 4C